Karakteristik dan Kinerja Subakabian di Tiga Kabupaten Anggota MPIG Kopi Arabika Kintamani - Swastawan, I Putu Edi; Suamba, Ketut; Windia, Wayan (JURNAL MANAJEMEN AGRIBISNIS, 2022)
Compared to subak, subakabian literature/study is still rarely considered in development. In fact, sub-abian plays an important role in the development of one of the leading commodities in Bali, namely Kintamani Arabica Coffee which has received geographical indication certification since 2008. This study aims to analyze the characteristics and performance of sub-abian in the three regencies of MPIG Kintamani Arabica Coffee, as well as compare the characteristics and subakabian performance between the three districts. Characteristics and performance of the subakabian were identified based on Mackay's theory, then analyzed qualitatively and quantitatively through the RRA approach and the calculation of economic impact analysis. The results showed that the subakabians in the research location had the characteristics of binding each other with the traditional village; have the right of autonomy; adaptive to technological developments; subakabaian manners are bound by professional, geographical, and historical unity; based on the philosophy of tri hita karana; based on the principles of togetherness and mutual cooperation; leadership and decision-making are democratic; neoclassical agricultural organization with low formalization; and legal norms with dominant social meaning in subakabian, namely customary law. Subakabian's performance has been effective in achieving its goals and efficiently using resources so as to be able to provide local economic impact. Differences in subakabian members of the Kintamani Arabica Coffee MPIG between Bangli Districts; Buleleng Regency; and Badung Regency is only concerned with local government support and technical implementation of social culture.